Contract Agreement Literacy among Creative Industry Practitioners in Supporting the Gig Economy in Malaysia - Mohamad Isa, Siti Fariza (UMSU, 2025)
Statistics suggest that the gig economy contributors are from the age group of youths and young adults. Therefore, the gig economy’s ecosystem offers a pay-per-job work concept that doesn’t require any prolonged relationship between the stakeholders. The unmatured experience in conducting business and involvement causes effects such as a lot of these young creative industry practitioners have lack of knowledge and literacy of how contract agreements should be curated in order to secure their moral and economic well-being. The objective of this study is to understand the contributing factors of lack of knowledge of contract agreement produce and how the expansive literacy of it have the potential to contribute to the longevity of wealth sustainability in the gig economy. This study was conducted in a qualitative method with two (2) types of interviews which were one-to-one interviews and webinar with six (6) informants in total. The qualitative data was then transcribed verbatim and analysed using the website version of ATLAS.ti with the outcome of three (3) themes that emerged from the study. The findings of the study suggests that the importance of contract agreement literacy would strengthen the creative industry practitioner’s economic well-being in the long-run.